NEFROLITIASIS PADA ANAK USIA TIGA TAHUN DI RSUD DR. HI. ABDUL MOELOEK, LAMPUNG: SEBUAH LAPORAN KASUS - Angga Hendro Priyono; Exsa Hadibrata (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2019)
ABSTRACT Background: The incidence of nephrolithiasis in children increases over time. It has been reported an increase of 6 to 10% per year for the last twenty-five years. Research in developing country showed that urinary tract infection and metabolic disorders were the caused of nephrolithiasis. Illustration Case: Three years 10 months old boy had a complaint of pain in plank region followed by tea-like urine since two months ago. Physical examination showed that he appeared to be moderately ill and compos mentis. His physical examinations were normal except positive ballotement and positive costoverebral angle (CVA) pain in the right flank region. Laboratory finding showed positive eritrocyte in urinalysis. Ultrasonography and abdominal CT-scan consistent with nephrolithiasis. Management: Pyelolitotomy was performed under general anesthesia. Postoperatively, patient treated in a pediatric surgery room and observation was carried out. He was given D5NS 500 ml administered 20 drops per minute microdrip IV, paracetamol 3 x 225 mg IV, and cefotaxime injection 2 x 500 mg IV after a skin test first. Result and Follow Up: An irregular stone 1,5 cm x 1 cm in size consist of 45% ammonium urate, 31% sodium urate monohydrate, and 24% amorphous calcium phosphate carbonate was found. Discussion: Nephrolithiasis in children occurs due to several related conditions such as genetics, ethnicity, climate, and nutrition. Complications can be prevented by managing and controlling appropriate risk factors.